Histopathological evaluation of green betel leaf extract ointment on incision wounds infected with Staphylococcus aureus in wistar rats - Winda Irawati Zebua; Linda Chiuman; Edy Fachrial (Jurnal Teknologi Laboratorium)
The skin, as the largest organ in both humans and animals, functions as a protective barrier against various external threats such as sharp objects, temperature fluctuations, chemicals, and physical trauma. Incision wounds are particularly vulnerable to infections, with Staphylococcus aureus being a common causative agent of secondary complications, including prolonged inflammation and delayed healing. This study investigates the efficacy of green betel leaf extract ointment in accelerating the healing process of incision wounds in Wistar rats infected with Staphylococcus aureus. An experimental, post-test-only controlled group design was employed, involving five groups of five rats each. The groups were treated with an ointment base (control), mupirocin ointment (positive control), and green betel leaf extract ointments at concentrations of 10%, 15%, and 20%. Data were analyzed using normality tests, homogeneity tests, and ANOVA. Phytochemical analysis revealed that green betel leaf extract contains alkaloids, terpenoids/steroids, saponins, tannins, and glycosides, all of which are secondary metabolites known for their antimicrobial and wound healing properties. Among the treatment groups, the 15% green betel leaf extract ointment exhibited the most rapid wound closure (average wound healing of 1.44 mm), approaching the effectiveness of mupirocin ointment. Histopathological observations further demonstrated a significant increase in epithelialization and fibroblast proliferation in treated groups compared to controls. In conclusion, green betel leaf extract ointment, particularly at a 15% concentration, shows promising potential as a topical agent for treating Staphylococcus aureus-infected incision wounds in Wistar rats.